1997
DOI: 10.1034/j.1600-0501.1997.080601.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration enhanced by chemical etching of the titanium surface. A torque removal study in the rabbit.

Abstract: Roughened implant surfaces are thought to enhance osseointegration. Torque removal forces have been used as a biomechanical measure of anchorage or osseointegration in which the greater forces required to remove implants may be interpreted as an increase in the strength of osseointegration. The purpose of this study was to compare the torque resistance to removal of screw shaped titanium implants having an acid etched (HC1/H2SO4) surface (Osseotite) with implants having a machined surface. Two custom screw sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
191
4
14

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(216 citation statements)
references
References 0 publications
7
191
4
14
Order By: Relevance
“…So, our results contradict studies that found a higher primary stability at treated implants 8,[19][20] . However, our results can be explained by Cunha et al 21 , who concluded that the design is more important than the surface for primary stability, when verified that the stability of machined implants was the highest of those treated.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…So, our results contradict studies that found a higher primary stability at treated implants 8,[19][20] . However, our results can be explained by Cunha et al 21 , who concluded that the design is more important than the surface for primary stability, when verified that the stability of machined implants was the highest of those treated.…”
Section: Discussioncontrasting
confidence: 56%
“…Statistically, the Master Porous and Master Screw implants were equals in the insertion torque of all densities and shows that the presence of surface treatment did not influence the results, despite having selected the use of machined implants (Master Screw and Conect Cônico) as negative control, due to better biomechanical characteristics of the treated implants, which its surface roughness, theoretically promotes a larger area of bone-implant contact [18][19] . So, our results contradict studies that found a higher primary stability at treated implants 8,[19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Initial biofilm formation may be influenced by the implant surface and the adhesion of microorganisms seems to be directly proportional to surface roughness 35,43,[45][46][47][48][49][50][51] . Other studies also confirm the relationship between surface roughness and the efficiency for osseointegration [52][53][54][55] . Thus, the rougher the surface, the larger the accumulation of biofilm 46,48 , and the greater the chances for clinical failure due to the interplay between these factors.…”
Section: Resultsmentioning
confidence: 53%
“…The relationship between surface treatment with nitric acid etching (E) and the lower amount of microorganisms in the first two assessment periods (12 and 24 hours) may be associated with a decrease in roughness, compared to groups where sand-blasted was used, due to the acid etching process, or to a possible antimicrobial property of the nitric acid. Some studies aimed to maximize the quantity and quality of the bone-implant interface, reported that several changes in the implant surface have been proposed, most of them based on the assumption that a better and quicker osseointegration may be achieved by changing the topography or roughness of the implant 52,53,59 . Since the R a values found in the present study were different between the groups, biological results may not have been influenced by roughness according to the experimental periods assessed (48 to 168 hours) but rather by factors such as irregular surface topography, surface contamination by aluminum (Al) particles or possible changes in the surface energy of the metal by the surface treatments used.…”
mentioning
confidence: 99%
“…Studies have shown that Ti implants with adequate roughness may enhance bone-to-implant contact [6] and increase the removal torque force [7][8][9]. Elias et al [10] analyzed different methods for increasing surface roughness and improving dental implant osseointegration.…”
Section: Introductionmentioning
confidence: 99%